ADDITION OF ANTI- Toxoplasma gondii MEMBRANE IMMUNOGLOBULIN Y TO REDUCE NECROTIC INDEX IN MICE’S LIVER - Puspitasari, Heni; Suwanti, Lucia T.; Djaeri, Mufasirin (African Journal of Infectious Diseases (AJID), 2018)
Background The study aimes to determine the effect of administering anti-T. gondii membrane IgY against liver damage (Necrotic index) and the effectiveness of the antibody’s delivery time. Materials and Methods This research was a laboratory experiment with five treatments and five replicantions. Each treatment used female mice (Mus musculus) as animal models. The treatment groups consisted of a P0 group (not infected), P1 group (infected), P2 group (anti- T. gondii membrane IgY given one day before infection), P3 group (anti-T. gondii membrane IgY given together with infection) and P4 group (anti-T. gondii membrane IgY given two days after the infection. A dose of anti- T. gondii membrane IgY as many as 75 ug/head and infectious dose of 10 tachyzoites/head were given. Four days after infection mice were sacrified and examined. Finally, necrotic index in histopathological liver using Hematoxylin Eosin. Results The percentage of necrotic index liver showed that result treatment of P2 and P3 treatment that lower than another treatment. Conclusion Thus, it can be concluded that administration of anti-T. gondii membrane IgY can reduce liver cell necrotic index and it was greatest when given before and simultaneously with infection.